1989
DOI: 10.1093/oxfordjournals.aje.a115132
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Before Age 45 and Oral Contraceptive Use: New Findings

Abstract: The relation between the risk of breast cancer before 45 years of age and oral contraceptive use was examined in a case-control study conducted in New York, Philadelphia, Baltimore, and Boston from 1983 to 1986 of 407 patients with breast cancer and 424 controls. With allowance for confounding, for ever use, the multivariate relative risk estimate was 2.0 (95% confidence interval (CI), 1.4-2.9). For less than 10 years of use, the estimate approximated 2.0 in all categories of duration, including less than thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
1
6

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(39 citation statements)
references
References 0 publications
0
32
1
6
Order By: Relevance
“…To investigate the role of cyclical mastalgia as a potential precocious marker of breast steroid susceptibility in relation (Pike et al, 1983;Cancer and Steroid Hormone Study (CASH), 1986;MacPherson et al, 1987b;Miller et al, 1989;Olsson et al, 1989;Stadel et al, 1989;UK National Case-Control Study Group, 1989;Clavel et al, 1991 Oral contraceptive uses were elicited by constructing a monthly calendar of events starting at menarche up to the time of the interview. Contraceptive use was associated with marking events like first sexual intercourse, marriage, FFTP.…”
mentioning
confidence: 99%
“…To investigate the role of cyclical mastalgia as a potential precocious marker of breast steroid susceptibility in relation (Pike et al, 1983;Cancer and Steroid Hormone Study (CASH), 1986;MacPherson et al, 1987b;Miller et al, 1989;Olsson et al, 1989;Stadel et al, 1989;UK National Case-Control Study Group, 1989;Clavel et al, 1991 Oral contraceptive uses were elicited by constructing a monthly calendar of events starting at menarche up to the time of the interview. Contraceptive use was associated with marking events like first sexual intercourse, marriage, FFTP.…”
mentioning
confidence: 99%
“…The relative risks given are those for the longest duration of use group and significant trends in relative risk are indicated. While some authors have reported no significant increases in risk of breast cancer associated with oral contraceptive use (Vessey et al, 1982Stadel et al, 1985;Miller et al, 1986;Paul et al, 1986;Jick et al, 1989), others have suggested the presence ofan increased risk; no study shows any evidence of a protective effect.…”
Section: Biasmentioning
confidence: 98%
“…Most recent studies have used aids to recall, such as a calendar of life events and photographs of the packaging of brands of oral contraceptives, both of which have been shown to improve accuracy of recall (Coulter et al, 1986). These cannot be used directly in telephone interviews although Paul et al (1986) (Pike et al, 1981(Pike et al, , 1983Vessey et al, 1982Vessey et al, , 1983Miller et al, 1986;Meirik et al, 1986;McPherson et al, 1987;Jick et al, 1989; UK National Case-Control Study Group, 1989), while others have formally or informally frequency matched the case and control age distributions (Rosenberg et al, 1984;Stadel et al, 1985;Paul et al, 1986;Miller et al, 1989;WHO, 1989) and subsequently controlled for age during analysis. However, matching or stratification has not always been performed within narrow age bands, only two studies having employed very close individual matching on age (Meirik et al, 1986; UK National Case-Control Study Group, 1989) and both of these report a positive association between total oral contraceptive use and breast cancer risk.…”
mentioning
confidence: 99%
“…Although not aIl studies have found an increased risk ofbreast cancer in oral contraceptive users, several have (60)(61)(62)(63)(64)(65)(66)(67). (GeneraIly subjects were considered as exposed ifthe pills were taken for at least 6 months, and compared to "non-users".)…”
Section: Ii) Cancer Ascertainment In Cohort Studiesmentioning
confidence: 99%